The mediating role of depression in the association between health-related quality of life and suicidal ideation in adolescents: findings from a longitudinal study - Preisig, Martina; Häberling, Isabelle; Smigielski, Lukasz; Emery, Sophie; Baumgartner, Noemi; Albermann, Mona; Strumberger, Michael; Schmeck, Klaus; Wöckel, Lars; Erb, Suzanne; Rhiner, Bruno; Contin-Waldvogel, Brigitte; et al. (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionAdolescent suicidality is a significant public health issue. To develop effective interventions aimed at preventing suicide in this vulnerable population, it is essential to understand the complex interplay of health-related quality of life, depression and suicidal ideation.MethodsFor this purpose, we analyzed longitudinal data of 250 children and adolescents diagnosed with major depressive disorder (M = 15.7, SD = 1.6, range 8–18 years, 74% females). The main goal of the study was to examine whether the effect of health-related quality of life on individual trajectories of suicidal ideation is mediated by depression severity. A series of t-tests, Chi-squared-tests, Fisher’s exact tests and a mediation analysis including three robust linear mixed-effects models were conducted.ResultsDepressed adolescents with suicidal ideation reported lower health-related quality of life across physical, psychological, peer, and school domains compared to those without suicidal ideation, while no significant difference was observed in the family-related domain. Psychological well-being emerged as the sole domain of health-related quality of life with a direct influence on suicidal ideation. Notably, depression severity mediated the effect of physical, psychological, peer- and school-related quality of life on suicidal ideation.DiscussionOur findings suggest that improving health-related quality of life reduces depressive symptoms, which in turn leads to lower suicidal ideation. This highlights the importance of including health-related quality of life in the clinical assessment of suicide risk as well as targeting health-related quality of life in therapeutic interventions. In the light of the results of this study, interventions should not only focus on classical clinical criteria of psychiatric diagnoses such as major depressive disorder, but also on broader, more resource-oriented constructs such as health-related quality of life to better mitigate the risk of suicide in this vulnerable population. Clinical Trial Registrationwww.ClinicalTrials.gov, identifier [NCT03167307].